Pengaruh Penambahan Ion Mg2+ Terhadap Kandungan Lipid Fitoplankton Chlorella vulgaris Sebagai Bahan Baku Pembuatan Biodiesel dengan Metode Ultrasonik - Alfani M Datu; Indah Raya; Muhammad Zakir (Hasanuddin University, 2013)
An investigation on the effect of Mg2+ on its lipid content from phytoplankton Chlorella vulgaris as a raw material for producing biodiesel by ultrasonic method has been carried out. The results showed that Mg2+ is good as a nutrient for phytoplankton. The optimum concentration was 0.4 ppm. Total of dry biomass was 32.7902 grams. Lipid was extracted by ultrasonic method using ethanol 95% as solvent. Biodiesels were syntesized in two steps namely esterification by methanol solvent and H2SO4 as catalyst, folowed by transesterification by using methanol solvent with KOH as a catalyst. Total of biodiesel made was 11.5727 grams and the yield was 35.29%. The result of biodiesel characterised in term of physical and chemical characteristics including: density, viscosity, free fatty acid, saponification value, and iodine value, respectively. Result of the analysis showed that biodiesel characteristics have fulfilled standard the American Society for Testing and Materials (ASTM D6751), except value of density and Free Fatty Acid.